Analisis Komunikasi Hasil Audit pada Koperasi Simpan Pinjam dan Pembiayaan Syariah(KPPS) - Arum Ardianingsih (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
Cooperatives prepare financial reports as the basis for accountability of managers and administrators to members based on financial accounting standards for entites without public accountability (SAK ETAP). Cooperatives require an audit from an eksternal auditor to ensure the fairness of the presentations of their financial statements. Supervision of Islamic microfinance institutions is in two bodies, namely the financial services authority(OJK) and the ministry of cooperatives and micro, small and medium enterprises(MSMEs). Supervision under the ministry of cooperatives and micro, small and medium enterprises(MSMEs), the Sharia`s saving and loans cooperatives(KPPS) in preparing their financial reports refers to the financial accounting standards of entities without public accountability(SAK ETAP). Statement of sharia financial accounting standards(PSAK) for related transactions. KPPS Nusa Kartika has been operating approximately twelve years ago. This research is a qualitative research with a case study approach. The research object is KPPS Nusa Kartika. Research data was taken by conducting observations, interviews and direct participation of researches. The audit findings are communicated proactively to KPPS managers and administrators. KPPS Nusa Kartika management and management have the commitment and integrity to make corrections and follow up on audit findings.